2021
DOI: 10.3390/electronics10202552
|View full text |Cite
|
Sign up to set email alerts
|

SEOUL AR: Designing a Mobile AR Tour Application for Seoul Sky Observatory in South Korea

Abstract: Skyscrapers are symbols of local landmarks, and their prevalence is increasing across the world owing to recent advances in architectural technology. In Korea, the Lotte World Tower, which is now the tallest skyscraper in Seoul, was constructed in 2017. In addition, it has an observatory deck called Seoul Sky, which is currently in operation. This study focuses on the design of Seoul AR, which is a mobile augmented reality (AR) tour application. Visitors can use Seoul AR when visiting the Seoul Sky Observatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In particular, in-stream video ads viewers' visual attention may shift out of the screen or toward non-ad-related content, such as the video player's controls, the timer, the skip button, and if the player is not in full-screen mode, also towards recommendations for similar content, titles, and comments [59]. However, the users' capacity to adapt to, identify, and ignore digital advertising [57,[60][61][62][63][64][65][66] followed by avoiding behaviors, such as shifting attention towards regions of the screen where the advertising content is not salient [67,68], is not the only factor leading to reduced visual attention towards the advertising content. In this direction, an eye-tracking study conducted by Kim et al (2023) [68] on mobile in-stream video ads suggested that, while watching non-skippable ads, viewers' visual attention tends to highly focus on the timer because viewers aim to figure out how long they are "forced" to watch the ad before resuming the original video, reflecting the need for temporal certainty.…”
Section: Visual Attention and In-stream Video Adsmentioning
confidence: 99%
“…In particular, in-stream video ads viewers' visual attention may shift out of the screen or toward non-ad-related content, such as the video player's controls, the timer, the skip button, and if the player is not in full-screen mode, also towards recommendations for similar content, titles, and comments [59]. However, the users' capacity to adapt to, identify, and ignore digital advertising [57,[60][61][62][63][64][65][66] followed by avoiding behaviors, such as shifting attention towards regions of the screen where the advertising content is not salient [67,68], is not the only factor leading to reduced visual attention towards the advertising content. In this direction, an eye-tracking study conducted by Kim et al (2023) [68] on mobile in-stream video ads suggested that, while watching non-skippable ads, viewers' visual attention tends to highly focus on the timer because viewers aim to figure out how long they are "forced" to watch the ad before resuming the original video, reflecting the need for temporal certainty.…”
Section: Visual Attention and In-stream Video Adsmentioning
confidence: 99%
“…The majority of the studies, with 41 articles (71.93%), focus on outdoor settings, highlighting the potential of AR to enhance the experience of tourists visiting natural and urban environments [49]. In contrast, 11 articles (19.30%) explore indoor settings, such as museums, galleries, and historical buildings, demonstrating the value of augmented reality in providing immersive experiences within confined spaces (e.g., [50]). Additionally, 2 articles (3.51%) investigate the combined use of AR technology in both indoor and outdoor environments, emphasizing the versatility of the technology [51,52].…”
Section: Tourism Settingsmentioning
confidence: 99%
“…[85] presented two location-based AR systems that employed both smartphones and smart glasses, enabling users to access audio and visual information when arriving at a point of interest. Handheld 39 [28,43,45,[48][49][50][51][53][54][55]58,59,[61][62][63][64][65]67,68,[71][72][73][74][75][76][79][80][81]83,84,[86][87][88][89][90][93][94][95][96] 2 [35,60] 0 0 0 8 [44,46,52,69,70,77,85,92] HMD 3…”
Section: Links Between Ar Devices and Virtual Contentmentioning
confidence: 99%